Nestle, A Staple Brand in Everyone's Life: A Case Study on Brand Loyalty - Lin Sia, Tanisha Shi; Teh, Pei Ju; Teng, Wen Hui; Munirah, Tengku Awatif; Almutairi, Noura; Shuaib, Manayer (AIBPM Publisher, 2022)
Nestle is one of the leading food companies in the world. We aim to investigate how product quality, brand name, advertisement, and product price influence customer loyalty. We tested our hypotheses by examining 100 Malaysian consumers. We found that product quality and advertisement are positively related to customer loyalty. We also identify that advertisement is the most significant factor influencing customer loyalty. Given that advertisement is the most significant factor influencing customer loyalty, we conducted another survey in Kuwait to determine which advertisements influence consumer behavior, in which a total of 175 Kuwait consumers participated. The findings show consumer behavior is primarily impacted by TV advertisements and celebrity endorsements in their brand preference. The main reason for preferring Nestle products is their high product quality and advertising. Thus, Nestle is recommended to maintain its high quality and deal with celebrities for its advertisements to retain brand loyalty.Â Keywords: Advertising, Celebrity Endorsements, Customer Behaviour, Customer Loyalty, Product Quality, Purchase Decision.